The Influence of Personal Branding and Social Media Marketing on Brand Image with Brand Awareness as an Intervening Variable - Akbar, Tiara Arayni; Nurjanah, Siti (Marketing and Business Strategy, 2023)
Every business actor must decide the correct approach to survive in a competitive market. This study examined Erika Richardo's personal branding and social media marketing on By Painters brand image, using brand awareness as an intervening variable. Quantitative research uses non-probability sampling with purposive sampling in this study. The data collection approach consists of sending surveys to 100 Instagram followers of "By Painters." The hypothesis testing shows that personal branding does not affect brand awareness. Social media marketing affects brand awareness significantly. Personal branding and social media marketing also affect brand image. Brand image is also affected by brand awareness. Managerial implications highlight the need for painters and their managers to proactively invest in personal branding efforts and harness the power of social media for marketing. By doing this, they can not only increase brand awareness but also establish a positive brand image that resonates with the target audience. Continuous monitoring of brand awareness and consistent efforts to engage with the community are essential elements for maintaining and increasing brand presence in the competitive art market. This research uses a quantitative approach with primary resources. The sampling technique used was nonprobability sampling via the purposive sampling method.